A System Dynamics Pricing Model for Stabilizing Prices for Telecommunication Products and Services in Uganda - Mayoka, Kituyi; Moya, Musa; Rwashana, Agnes S. (International Scientific Research Journal, 2012)
This study involved the use of systems dynamics approach to develop a pricing model for telecommunication goods and services in Uganda. Primary data were collected from four telecommunication service providers and Uganda Communications Commission, a regulatory body of telecommunications in Uganda. Descriptive statistics and factor analysis with principal component and varimax rotation methods were used to determine the most important factors that affected the pricing decisions made by telecommunication firms. These factors were further analyzed and modeled using Vensim PLE simulation and modeling software, to develop a new pricing model for telecommunications goods and services. The findings indicate that demand and market based pricing approaches are the significant approaches used to set prices for telecommunication products and services in Uganda. The main factors affecting prices of telecommunication goods and service include operating costs, forces of demand and supply, foreign exchange rate, inflation and excessive competition. This paper presents four policy strategies for stable telecommunication prices as Taxation, Liberalization, Government incentives and Wealth maximization.
Keywords: System dynamics; Telecom prices; Pricing methods; Developing countries; Uganda